An anti-poisoning nanosensor for monitoring of intracellular endogenous hydrogen sulfide - Chen, Xi; Wu, Wen-Tao; Jiao, Yu-Ting; Kang, Yi-Ran; Zhang, Xin-Wei; Huang, Wei-Hua (Chemical communications (Cambridge, England), 2023)
Intracellular H 2 S plays an important regulatory role in cell metabolism. The limited sensing materials and severe sensor passivation hinder its quantification. We functionalized conductive nanowires with MoS 2 and quercetin in a large-scale manner, developed single nanowire sensors with excellent electrocatalytic and anti-poisoning performance, and achieved the accurate quantification of H 2 S within single cells. We develop MoS 2 and quercetin functionalized nanoelectrodes with excellent electrocatalytic and anti-sulfur poisoning performance for H 2 S detection. Utilizing such nanosensors, the accurate quantification of intracellular endogenous H 2 S was achieved.